The Hubungan minat belajar dan motivasi belajar dengan disiplin belajar Biologi siswa kelas XI MIPA SMA Negeri 4 Pekanbaru tahun ajaran 2020/2021: Hubungan minat belajar dan motivasi belajar dengan disiplin belajar Biologi siswa kelas XI MIPA SMA Negeri 4 Pekanbaru tahun ajaran 2020/2021 - Suryanti Suryanti; Afnila Fritadini Hariono; Sepita Ferazona (Biology and Education Journal, 2022)
The relationship of learning interest and learning motivation with the discipline of learning Biology of students in grade XI MIPA SMA Negeri 4 Pekanbaru academic year 2020/2021. This study aims to find out the relationship of learning interest and learning motivation with the discipline of learning biology of students in grade XI MIPA SMA Negeri 4 Pekanbaru school year 2020/2021. The research was conducted from Agust to December 2020. This research is a correlational research and data collection using questionnaires, interviews and documentation. The sample in this study was 113 randomized students or rondom sampling techniques. Data analysis in this study used Pearson Pruduct Moment correlation technique. The results found that interest in learning (X1) and learning motivation (X2) with learning discipline (Y) there is a high relationship (0.848). The significance test value was obtained that the interest in learning (X1) and learning motivation (X2) with the discipline of learning (Y), thitung (13.2) > ttabel (0.184). Furthermore, interest in learning (X1) and learning motivation (X2) contributed 61.1% to the discipline of learning (Y) to students of grade XI MIPA at SMA Negeri 4 Pekanbaru in the 2020/2021 school year.